Forecasting the Number of Visitors to the UIN Walisongo Semarang Library with the Decomposition Method - Eva Khoirun Nisa; Nawwarotul Jannah; Muhammad Amjed Iqbal (At-Taqaddum, 2022)
The library is an important part of a university. Especially for UIN Walisongo Semarang which states to be a research Islamic university based on the vision that has been announced. The library is a vital unit contributing to the realization of the vision of the institution because it is a storage place for various research results both from inside and outside UIN Walisongo Semarang. In addition, several problems occur in the library, so it is necessary to forecast the number of visitors to ascertain the number of librarians who serve it. Decomposition becomes a statistical method in predicting the number of visitors because this method breaks the components of a periodic series separately which can improve the accuracy of forecasting. This prediction has resulted in an increase in the number of visitors to the library of UIN Walisongo Semarang in 2020 compared to the previous year. Based on the results of forecasting the number of visitors, the number of librarians that must be provided is 42 librarians.